The middle-income transition around the globe: Characteristics of graduation and slowdown - Paul Vandenberg; Lilibeth Poot; Jeffrey Miyamoto (Asian Development Bank Institute (ADBI), 2015)
The paper investigates the situation of middle-income economies around the world. Since 1965, only 18 economies with a population of more than 3 million and not dependent on oil exports have made the transition to being high income. Many more have not been able to move beyond the middle-income stage. We conduct statistical tests of differences between two groups of economies across a range of growth and development variables. The results suggest that middle-income economies are particularly weak in the following areas: governance, infrastructure, savings and investment, inequality, and quality - but not quantity - of education. The findings are used to suggest whether the People's Republic of China is successfully progressing through the middle-income stage or whether it may get caught in a middle-income trap.
Keywords: O14; O33; O40; O53; 330; middle-income trap; transition; economic development; slowdown